RELATIONSHIP BETWEEN EMPLOYABILITY OF POSTGRADUATES OF SRI VENKATESWARA VETERINARY UNIVERSITY, TIRUPATI, ANDHRA PRADESH - M.V. Prasanna; G. Triveni; B. Subrahmanyeswari (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Employability refers to a person’s capability to gain employment, maintaining employment and obtain new employment if required in simple words, employability refers to one's capacity to obtain and maintain fulfilling work. The present study was undertaken with the main objective of ascertaining the employability of postgraduates of SVVU. Ex-post-facto research design was followed in the present investigation. Out of the total 479 postgraduate students a sample of 120 respondents were selected from each academic year through proportionate random sampling. In this research, to study and measure the employability of postgraduates, seven indicators based on the opinion of experts and review of literature was collected. The collected data were classified, tabulated, analysed and interpreted in order to make the findings meaningful. The statistical measures such as frequency, percentage, arithmetic mean and co-efficient of correlation were used in the study. It can be concluded that three-fourth (75%) of the postgraduates of SVVU had high to medium level of overall employability.